Butyric acid derived from Pantoea ananatis CE26 suppresses postharvest gray mold by inducing membrane disruption and oxidative stress of Botrytis cinerea - Yushan Du; Liwenqian Wang; Jingyuan Zhan; Nongyu Xia; Baoqing Zhu; Guangjin Li; Fengjun Wang (Food Bioscience, 2026)

CO2 bubble-regulated porous architecture of CS@ZIF-8 microspheres for enhanced alcalase immobilization with improved walnut protein hydrolysis - Jiangjuan Yuan; Xueying Liu; Mingyao Li; Feng Jin; Baokai Cui; Jingzhen Chen; Changzhu Li; Fengjun Wang (Carbohydrate Polymers, 2026)

Sandstone-hosted uranium mineral prospectivity mapping based on ResNet50 self-distillation - Weijian Zheng; Jianfeng He; Weidong Li; Fei Xia; Fengjun Nie; Zizheng Yu; Caijun Gong; Guoyun Zhong; Fan Diao (Computational Geosciences, 2026)

From structural remodeling to cytoprotection: pH-regulated assembly of walnut protein hydrolysate fibril-chlorogenic acid complexes and transcriptomic insights - Chang Li; Jiangjuan Yuan; Junyang Long; Feng Jin; Baokai Cui; Jingzhen Chen; Changzhu Li; Fengjun Wang (Food Bioscience, 2026)

Controls on aeolian source dominance in an inland sand sea: Insights from the Kumtagh Sand Sea - Aimin Liang; Xiaokang Liu; Ivan Lizaga; Zhengcai Zhang; Zhizhu Su; Bo Wu; Chao Li; Fengjun Xiao; Junliang Gao; Rongliang Liu; Zhibao Dong (CATENA, 2026)

BrNAC046 involved in hydrogen peroxide-induced leaf senescence of postharvest Chinese flowering cabbage - Fengjun Li; Baoxiang Ren; Lilang Li; Xiangjin Kong; Hanzhi Liang; Hai Liu; Ling Wang; Yueming Jiang (Postharvest Biology and Technology, 2026)

Biodegradable polybutylene adipate terephthalate packaging with dual-functionality: Synergistic effects of curcumin coating and laser micro-perforation on sweet cherry preservation - Zhijie Zuo; Xiao Chen; Ming Li; Xinhua Zhang; Binshan Mu; Yijing Li; Zhanjun Guo; Changfeng Zhang; Xinguang Fan; Fujun Li; Fengjun Guo (Food Packaging and Shelf Life, 2026)

Resveratrol-Eu-layered double hydroxide nanocomposite alleviates radiation-induced lung injury through antioxidant and IL-17/NF-κB-associated anti-inflammatory effects - Fangxiao Cao; Junzhe Yang; Xiaoyi Cai; Xin Zuo; Yiming Wang; Li Du; Yuxin Lu; Xiaochen Cheng; Tingting Liu; Shan Ma; Feiyu Zhao; Shanyue Guan; et al. (Chemical Engineering Journal, 2026)

Integrated physiological, transcriptomic and lipidomic analyses reveal the role of trans-2-octenal in the postharvest preservation of fresh walnut kernels - Jiamei Yuan; Yushan Du; Kun Zhang; Heyue Yang; Guangjin Li; Fengjun Wang (Postharvest Biology and Technology, 2026)

Efficacy and possible mechanism of trans-2-octenal in controlling grey mould caused by Botrytis cinerea on harvested fruit - Jiamei Yuan; Jie Yang; Yushan Du; Liwenqian Wang; Fengjun Wang; Guangjin Li (Postharvest Biology and Technology, 2026)

Flocoumafen exposure induces skeletal developmental toxicity and neurotoxicity in zebrafish (Danio rerio) - Tianyi Chen; Fengjun Fan; An Cheng; Yumei Xia; Haoze Chen; Jiakai Fang; Yangyu Chen; Tianjia Li; Anli Wang; Binjie Wang; Weixuan Yao; Yuanzhao Wu (Toxicology Letters, 2026)

Inhibition of postharvest soft rot in Chinese flowering cabbage by propyl gallate - Fengjun Li; Zhili Xu; Longlong Song; Lilang Li; Hai Liu; Yan Liao; Yuntao Zhao (Postharvest Biology and Technology, 2026)

Preparation of mesoporous polydopamine/thyme essential oil/fish scale gelatin photothermal antibacterial film and its application on cherry tomato preservation - Yunfeng Yang; Quanwen Liu; Peng Yang; Xiulian Li; Xiangquan Zeng; Fengjun Guo; Xinguang Fan (Food Chemistry, 2026)

Physiological and transcriptomic insights into low temperature-induced suppression of internal browning in postharvest pineapple (Ananas comosus L.) - Longlong Song; Zhili Xu; Fengjun Li; Hai Liu; Lilang Li; Yan Liao; Yuntao Zhao (Postharvest Biology and Technology, 2025)

Conservation tillage and wheat straw managements improve soil organic carbon sequestration via calcium-mediated microbial communities and aggregate stability in Calcaric Cambisols - Zixuan Han; Shengping Li; Aurore Degré; Huizhou Gao; Fengjun Zheng; Xiaojun Song; Angyuan Jia; Xueping Wu (Journal of Environmental Management, 2025)

Functional characterization of two CCL20 chemokines in black rockfish (Sebastes schlegelii): dual roles in immune cell recruitment and direct antimicrobial defense - Fengjun Lin; Yiying Liu; Chonghui Chen; Xiaoxu Zhang; Pei Zhang; Huijun Huo; Chao Li; Qiang Fu (Fish & Shellfish Immunology, 2025)

Establishment and characterization of a novel imatinib-resistant dermatofibrosarcoma protuberans cell line, DFSP-DPH1 - Hao Jiang; Kunqian He; Danli Li; Fengjun Zhu; Yuan Ren; Xinying Li; Yuanyuan Wang; Junbo Zhang; Yuangang Lu (Human Cell, 2025)

Responsive packaging that adapted to and regulated physiological metabolic of fruits and vegetables: Mechanism, application and prospects - Chunjun Chen; Yibing Ding; Yucong Feng; Xiulian Li; Chanchan Sun; Fengjun Guo; Xiangquan Zeng; Hansheng Gong; Xinguang Fan (Trends in Food Science & Technology, 2025)

A WRKY transcriptional factor, BrWRKY70, involves in stem lignification in postharvest Chinese flowering cabbage by regulating lignin synthesis - Fengjun Li; Ling Wang; Meiting Wu; Yulong Chen; Lilang Li; Hai Liu (Postharvest Biology and Technology, 2025)

The role of hydrolysis on the fibrillization of walnut protein: Self-assembly behavior, structural characteristics - Chang Li; Rui Chen; Jiangjuan Yuan; Feng Jin; Fengjun Wang (Food Chemistry, 2025)

Mapping the journey: Tracing the complete relocation trajectories of high-tech firms in the Pearl River Delta, China - Yuman Feng; Zhicong Ye; Li Ma; Fengjun Jin (Applied Geography, 2025)

Supplementation of exogenous RpfE facilitates polychlorinated biphenyl degradation in soil by stimulating endogenous rpfE expression and promoting cell growth - Hong Zou; Fengjun Xu; Xinyi Li; Yangyang Jia; Yulong Fu; Chaofeng Shen (Journal of Hazardous Materials, 2025)

The crosstalk between autophagy and apoptosis mechanism of hemocytes in Chlamys farreri under B[a]P exposure in vitro - Ning Zhang; Luqing Pan; Qilong Liao; Fengjun Lei; Ruixue Tong; Yaobing Li (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Unveiling interactions between anammox and denitrification from long-term steady-state scale and transient kinetic scale in a granular sludge system - Hao Tan; Fengjun Yin; Jinjin Zheng; Xuehai Yue; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Hong Liu (Bioresource Technology, 2025)

Electrochemical nitrite sensing using mass transfer signal with a catalyst-free small-sized rotating disk electrode for wastewater monitoring - Fengjun Yin; Xiaohui Yang; Shun Lu; Hanlin Zhang; Ying Zhao; Sha Wang; Cheng Song; Yongzhi Li; Zhaoming Chen; Hong Liu (Water Research, 2025)

Effects of Environmentally Friendly Aquaculture Chamber Coatings on Enzyme Activities, Histology, and Transcriptome in the Liver of Larimichthys crocea - Xuan Xu; Huayu Song; Huicai Wu; Lu Zhang; Fengjun Lin; Chonghui Chen; Xiaoxu Zhang; Yiying Liu; Chao Li; Qiang Fu (Marine Biotechnology, 2025)

Near-freezing temperature alters ROS metabolism and gene transcription to enhance peach chilling tolerance and aroma quality - Hongru Liu; Hui He; Qiankun Wang; Shaozhen Li; Fengjun Guo; Changfeng Zhang; Ke Wang; Chenxia Liu; Chunfang Wang; Xiao Wang; Bingjie Chen; Yi Zhang; et al. (Food Research International, 2025)

The source-specific health risk and biological effect assessment of PAHs in Mactra veneriformis from the Bohai Sea and Yellow Sea - Zeyuan Li; Ruicheng Qi; Jingjing Miao; Yufen Li; Qiaoqiao Wang; Fengjun Lei; Manni Wu; Yuanjing Chen; Luqing Pan (Environmental Pollution, 2025)

Digital twin comprehensive models: a study of ancient tree ecological environment quality assessment based on a cyber-physical system - Yansheng Chen; Huazhi Huang; Jie Li; Zejiong Zheng; Fengjun Gao; Xiaoge Han; Yanglin Gao (Environmental Monitoring and Assessment, 2025)

Biochar promotes the dissolution of inorganic inactive phosphorus by mediating the bacterial community during corn stover and cattle manure composting - Linqin Zhao; Ying Li; Bowen Fan; Mengmeng Wang; Ning Sun; Fengjun Yang (Chemosphere, 2025)

A structural equation model for assessing toxic effects of polycyclic aromatic hydrocarbons on scallop Chlamys farreri and the establishment of a novel integrated biomarker index - Zeyuan Li; Ruicheng Qi; Jingjing Miao; Yufen Li; Qiaoqiao Wang; Fengjun Lei; Manni Wu; Yuanjing Chen; Luqing Pan (Marine Environmental Research, 2025)

Identification and Validation of Lipid Metabolism Gene FASN-Associated miRNA in Wilms Tumor - Xiaoqing Wang; Xiao Li; Lin Tan; Fengjun Zhang; Jing Zhang; Xu Zhao; Yongfei Zhang; Guoqiang Du; Wei Liu (Biochemical Genetics, 2025)

Gallic acid reduces pericarp browning of litchi fruit during storage - Chunlan Wang; Shuting Zhang; Dandan Zhang; Fengjun Li; Lihong Xie; Tingrui Dai; Yueming Jiang (Postharvest Biology and Technology, 2025)

The preparation of fish scale gelatin-polydopamine photothermal sterilization film and its application for storage of cherry tomato - Yunfeng Yang; Xiulian Li; Ting Zhang; Xiangquan Zeng; Fengjun Guo; Quanwen Liu; Xinguang Fan; Da-Peng Yang (Food Packaging and Shelf Life, 2024)

Deciphering the potential of potassium-ion batteries beyond room temperature - Weihao Xia; Fengjun Ji; Yunzhuo Liu; Zhen Han; Kaikai Li; Jingyu Lu; Wei Zhai; Deping Li; Lijie Ci (Science Bulletin, 2024)

Observation of Low-Level Jets in the Eastern Tropical Indian Ocean Based on Shipborne Coherent Doppler Lidar - Haiyuan Wang; Lin Liu; Mengqi Fan; Yang Yang; Guang Yang; Yongliang Duan; Baochao Liu; Qinglei Su; Binbin Zhang; Fengjun Wang; Xuliang Shi; Qiuchi Li; et al. (Journal of Ocean University of China, 2024)

Host-derived lactic acid bacteria alleviate short beak and dwarf syndrome by preventing bone loss, intestinal barrier disruption, and inflammation - Mandi Liu; Fengjun Xiang; Jialu Pan; Yongzhi Xue; Maoyuan Sun; Kuan Zhao; Wuchao Zhang; Baishi Lei; Peipei Gao; Limin Li; Wanzhe Yuan (Veterinary Microbiology, 2024)

Walnut protein isolate-epigallocatechin gallate nanoparticles: A functional carrier enhanced stability and antioxidant activity of lycopene - Yuzhen Wang; Jiao Lv; Chang Li; Yizhuo Xu; Feng Jin; Fengjun Wang (Food Research International, 2024)

HCMV IE1/IE1mut Therapeutic Vaccine Induces Tumor Regression via Intratumoral Tertiary Lymphoid Structure Formation and Peripheral Immunity Activation in Glioblastoma Multiforme - Xiaoli Yang; Shasha Jiang; Fengjun Liu; Zonghui Li; Wenxuan Liu; Xianjuan Zhang; Fulong Nan; Jun Li; Meng Yu; Yunyang Wang; Bin Wang (Molecular Neurobiology, 2024)
Glioblastoma multiforme (GBM), a highly malignant invasive brain tumor, is associated with poor prognosis and survival and lacks an effective cure. High expression of the human cytomegalovirus (HCMV) immediate early protein 1 (IE1) in GBM tissues is strongly associated with their malignant progression, presenting a novel target for therapeutic strategies. Here, the bioluminescence imaging technology revealed remarkable tumor shrinkage and improved survival rates in a mouse glioma model treated with HCMV IE1/IE1mut vaccine. In addition, immunofluorescence data demonstrated that the treated group exhibited significantly more and larger tertiary lymphoid structures (TLSs) than the untreated group. The presence of TLS was associated with enhanced T cell infiltration, and a large number of proliferating T cells were found in the treated group. Furthermore, the flow cytometry results showed that in the treatment group, cytotoxic T lymphocytes exhibited partial polarization toward effector memory T cells and were activated to play a lethal role in the peripheral immunological organs. Furthermore, a substantial proportion of B cells in the draining lymph nodes expressed CD40 and CD86. Surprisingly, quantitative polymerase chain reaction indicated that a high expression of cytokines, including chemokines in brain tumors and immune tissues, induced the differentiation, development, and chemokine migration of immune cells in the treated group. Our study data demonstrate that IE1 or IE1mut vaccination has a favorable effect in glioma mice models. This study holds substantial implications for identifying new and effective therapeutic targets within GBM.

Long-term nitrogen fertilization enhances crop yield potential in no-tillage systems through enhancing soil fertility - Shengping Li; Xueping Wu; Xiaojun Song; Xiaotong Liu; Huizhou Gao; Guopeng Liang; Mengni Zhang; Fengjun Zheng; Peng Yang (Resources, Conservation and Recycling, 2024)

Biochar application can enhance phosphorus solubilization by strengthening redox properties of humic reducing microorganisms during composting - Bowen Fan; Changjiang Zhao; Liqin Zhao; Mengmeng Wang; Ning Sun; Zoutong Li; Fengjun Yang (Bioresource Technology, 2024)

Single-Cell RNA Sequencing Transcriptomics Revealed HCMV IE2-Related Microglia Responses in Alzheimer’s-Like Disease in Transgenic Mice - Fengjun Liu; Zhifei Wang; Delei Niu; Xianjuan Zhang; Fulong Nan; Shasha Jiang; Jun Li; Meng Yu; Xiaoli Yang; Shuyun Zhang; Xiaoqiong Zhou; Hui Wang; et al. (Molecular Neurobiology, 2024)
Although multiple factors are known to concur with Alzheimer’s disease (AD), the relationship between human cytomegalovirus (HCMV) and AD-like disease is unclear. Here, we propose a hypothesis that HCMV immediate-early 2 (IE2) protein promotes microglia activation and thus leads to AD-like disease. We successfully constructed IE2 transgenic mice expressing IE2 in the hippocampus. Single-cell sequencing analysis revealed that IE2 promoted the activation of microglia and upregulated the expression of disease-associated microglia genes. Differentially expressed gene analysis and pathway enrichment revealed that IE2 upregulated immune and nervous system disease-related genes. Immunohistochemical analysis showed that the expressions of both amyloid precursor protein (APP) and p-Tau were significantly upregulated in the brains of IE2 mice and were markers of AD. Taken together, these findings provide useful insights into AD-like disease activated by HCMV IE2.

Newcastle disease virus suppresses antigen presentation via inhibiting IL-12 expression in dendritic cells - Fulong Nan; Wenlong Nan; Xin Yan; Hui Wang; Shasha Jiang; Shuyun Zhang; Zhongjie Yu; Xianjuan Zhang; Fengjun Liu; Jun Li; Xiaoqiong Zhou; Delei Niu; et al. (Journal of Zhejiang University-SCIENCE B, 2024)

Path dependence or path creation of mature resource-based cities: A new firm entry perspective - Huijuan Sun; Li Ma; Fengjun Jin; Yujin Huang (Journal of Geographical Sciences, 2024)

Evaluation of toxicity of heated tobacco products aerosol and cigarette smoke to BEAS-2B cells based on 3D biomimetic chip model - Hongjuan Wang; Fengjun Lu; Yushan Tian; Sen Zhang; Shulei Han; Yaning Fu; Jun Li; Pengxia Feng; Zhihao Shi; Huan Chen; Hongwei Hou (Toxicology in Vitro, 2024)

Microbial regulation of aggregate stability and carbon sequestration under long-term conservation tillage and nitrogen application - Mengni Zhang; Xiaojun Song; Xueping Wu; Fengjun Zheng; Shengping Li; Yan Zhuang; Xvlun Man; Aurore Degré (Sustainable Production and Consumption, 2024)

Identification and stability evaluation of polyphenol oxidase substrates of pineapple fruit - Hai Liu; Jiangming Li; Yueming Jiang; Fengjun Li (Food Chemistry, 2024)

The immunotoxicity mechanism of hemocytes in Chlamys farreri incubated with noradrenaline and benzo[a]pyrene-7,8-dihydrodiol-9,10-epoxide alone or in combination - Qilong Liao; Fengjun Lei; Ning Zhang; Jingjing Miao; Ruixue Tong; Yaobing Li; Luqing Pan (Fish & Shellfish Immunology, 2024)

2D flake-like garnet electrolytes for solid-state lithium metal batteries - Jun Cheng; Yixuan Guo; Hongqiang Zhang; Fengjun Ji; Xuan Zhou; Zhen Zeng; Hongbin Liu; Qing Sun; Deping Li; Lijie Ci (Chemical Engineering Journal, 2024)

A comprehensive assessment framework for the risk and source of polycyclic aromatic hydrocarbons (PAHs) using two weight of evidence (WOE) approaches in bays of Shandong Province, China - Zeyuan Li; Ruicheng Qi; Jingjing Miao; Yufen Li; Qiaoqiao Wang; Fengjun Lei; Manni Wu; Yuanjing Chen; Luqing Pan (Journal of Cleaner Production, 2023)

Strong links between aggregate stability, soil carbon stocks and microbial community composition across management practices in a Chinese dryland cropping system - Fengjun Zheng; Xiaotong Liu; Mengni Zhang; Shengping Li; Xiaojun Song; Bisheng Wang; Xueping Wu; Kees Jan van Groenigen (CATENA, 2023)

Positive effects of crop rotation on soil aggregation and associated organic carbon are mainly controlled by climate and initial soil carbon content: A meta-analysis - Fengjun Zheng; Xiaotong Liu; Weiting Ding; Xiaojun Song; Shengping Li; Xueping Wu (Agriculture, Ecosystems & Environment, 2023)

Potential pathway and mechanisms underlining the immunotoxicity of benzo[a]pyrene to Chlamys farreri - Fengjun Lei; Ning Zhang; Jingjing Miao; Ruixue Tong; Yaobing Li; Luqing Pan (Environmental Science and Pollution Research, 2023)

Exosomal miR-17–92 derived from human mesenchymal stem cells promotes wound healing by enhancing angiogenesis and inhibiting endothelial cell ferroptosis - Wenbo Nie; Xuemiao Huang; Lijing Zhao; Taiwei Wang; Dan Zhang; Tianxin Xu; Lin Du; Yuxiang Li; Weiyuan Zhang; Fengjun Xiao; Lisheng Wang (Tissue and Cell, 2023)

Metagenomic analysis reveals the short-term influences on conjugation of blaNDM-1 and microbiome in hospital wastewater by silver nanoparticles at environmental-related concentration - Haichen Wang; Changhang Min; Fengjun Xia; Yubing Xia; Mengli Tang; Jun Li; Yongmei Hu; Mingxiang Zou (Environmental Research, 2023)

Adaptive Graph-Learning Convolutional Network for Multi-Node Offshore Wind Speed Forecasting - Jingjing Liu; Xinli Yang; Denghui Zhang; Ping Xu; Zhuolin Li; Fengjun Hu (Journal of Marine Science and Engineering, 2023)
Multi-node wind speed forecasting is greatly important for offshore wind power. It is a challenging task due to unknown complex spatial dependencies. Recently, graph neural networks (GNN) have been applied to wind forecasting because of their capability in modeling dependencies. However, existing methods usually require a pre-defined graph structure, which is not optimal for the downstream task and limits the application scope of GNN. In this paper, we propose adaptive graph-learning convolutional networks (AGLCN) that can automatically infer hidden associations among multi-nodes through a graph-learning module. It simultaneously integrates the temporal and graph convolutional modules to capture temporal and spatial features in the data. Experiments are conducted on real-world multi-node wind speed data from the China Sea. The results show that our model achieves state-of-the-art results in all multi-scale wind speed predictions. Moreover, the learned graph can reveal spatial correlations from a data-driven perspective.

Promotion and inhibition effects of wax on methane hydrate formation and dissociation in water-in-oil emulsions - Shikun Tong; Pengfei Li; Fengjun Lv; Zhiyuan Wang; Weiqi Fu; Jianbo Zhang; Litao Chen; Xuerui Wang (Fuel, 2023)

Extended lag phase indicates the dormancy of biphenyl degrading Rhodococcus biphenylivorans TG9 under heat stress - Jiahui Fan; Jinsong Feng; Dongdong Xu; Xinyi Li; Fengjun Xu; Haoming Li; Chaofeng Shen (Environmental Pollution, 2023)

Synergistic and antagonistic effects of preharvest salicylic acid and postharvest 1-methylcyclopropene treatments on the storage quality of apricot - Changchang Liang; Xinzhi Cui; Chanchan Sun; Sunxiang Ye; Ningxin Huang; Rong Chen; Aidi Zhang; Yanqing Yang; Hansheng Gong; Shuyang Sun; Fengjun Guo; Xinguang Fan; et al. (Food Chemistry, 2023)

A NAC transcriptional factor BrNAC029 is involved in cytokinin-delayed leaf senescence in postharvest Chinese flowering cabbage - Fengjun Li; Youxia Shan; Haobin Wang; Guoxiang Jiang; Xiaochun Ding; Hanzhi Liang; Chunlan Wang; Xiangjin Kong; Lihong Xie; Yueming Jiang (Food Chemistry, 2023)

Roles of Multisourced Fluids in the Formation of Sandstone-Hosted Uranium Deposits in the SW Songliao Basin, NE China - Zhibing Feng; Fengjun Nie; Li Jiang; Fei Xia; Jianfang Cai; Bocheng Zhang; Yayun Lu; Liangliang Zhang (Journal of Earth Science, 2023)

Accumulated temperature and allocation of photo-thermal resources are key meteorological factors affecting rice cadmium content - Wei Zhou; Fengjun Yan; Yu Fan; Chi Zhang; Fan Yang; Qi Liu; Tao Wang; Bo Li; Yong Chen; Fei Deng; Jianfeng Hu; Xiaolong Lei; et al. (European Journal of Agronomy, 2023)

Improving yield and nitrogen use efficiency of hybrid indica rice through optimizing nitrogen application strategies in the rice season under different rotation patterns - YongJian Sun; Dan Lin; YuanYuan Sun; FengJun Yan; Peng Ma; ChangChun Guo; FeiJie Li; ZhiYuan Yang; FuXian Xu; Jun Ma (Paddy and Water Environment, 2023)

Finite-/fixed-time synchronization for Cohen–Grossberg neural networks with discontinuous or continuous activations via periodically switching control - Hao Pu; Fengjun Li (Cognitive Neurodynamics, 2022)

Mesozoic intracontinental deformation of the Alxa Block in the middle part of Central Asian Orogenic Belt: A review - Jin Zhang; Yannan Wang; Junfeng Qu; Beihang Zhang; Heng Zhao; Long Yun; Tianyi Li; Pengfei Niu; Fengjun Nie; Jie Hui; Yiping Zhang (International Geology Review, 2021)

Dental Pulp Stem Cell-Derived Extracellular Vesicles Mitigate Haematopoietic Damage after Radiation - Fanxuan Kong; Chu-Tse Wu; Panpan Geng; Chao Liu; Fengjun Xiao; Li-Sheng Wang; Hua Wang (Stem Cell Reviews and Reports, 2021)
Radiation therapy can cause haematopoietic damage, and mesenchymal stem cells (MSCs) derived extracellular vesicles (EVs) have been shown to reverse this damage. Our previous research showed that dental pulp stem cells (DPSCs) have a strong proliferation capacity and can produce abundant amounts of EVs to meet the requirements for use in vitro and in vivo. DPSCs derived EVs (DPSCs-EVs) are evaluated for their effect on reducing haematopoietic damage. Haematopoietic stem cell (HSC) numbers and function were assessed by flow cytometry, peripheral blood cell counts, histology and bone marrow transplantation. Epidermal growth factor (EGF) was used as a reference for evaluating the efficiency of EVs. miRNA microarray was employed to find out the changes of miRNA expression after cells being irradiated in vivo and the role they may play in mitigation the radiation caused injury. We observed the effect of DPSCs-EVs on promoting proliferation and inhibiting apoptosis of human umbilical vein endothelial cells (HUVECs) and FDC-P1 cells in vitro. We found that DPSCs-EVs and EGF could comparably inhibit the decrease in WBC, CFU count and KSL cells in vivo. We also verified that EVs could accelerate the recovery of long-term HSCs. In summary, DPSCs-EVs showed an apoptosis resistant effect on HUVECs and FDC-P1 cells after radiation injury in vitro. EVs from DPSCs were comparable to EGF in their ability to regulate haematopoietic regeneration after radiation injury in vivo. Radiation could alter the expression of some miRNAs in bone marrow cells, and EVs could correct these changes to some extent.

Characterization of microsatellites in the endangered snow leopard based on the chromosome-level genome - Chuang Zhou; Fengjun Li; Qinchao Wen; Megan Price; Nan Yang; Bisong Yue (Mammal Research, 2021)

Complete mitochondrial genome of the Himalayan Musk Deer, Moschus leucogaster, with phylogenetic implication - Keji Guo; Fengjun Li; Qi Zhang; Shunde Chen (Conservation Genetics Resources, 2019)

Complete mitochondrial genome of the Himalayan Monal Lophophorus impejanus (Phasianidae), with phylogenetic implication - Yang Chen; Fengjun Li; Qi Zhang; Qiong Wang (Conservation Genetics Resources, 2018)

Fenofibrate ameliorates diabetic retinopathy by modulating Nrf2 signaling and NLRP3 inflammasome activation - Qiuping Liu; Fengjun Zhang; Xian Zhang; Rui Cheng; Jian-xing Ma; Jinglin Yi; Jingming Li (Molecular and Cellular Biochemistry, 2018)

Complete mitochondrial genome of the Burmese Short-Tailed Shrew, Blarinella wardi (Mammalia, Soricidae) - Fengjun Li; Xuming Wang; Qi Zhang; Haijun Jiang; Haixue Wei; Qing Wang; Shunde Chen; Shaoying Liu (Conservation Genetics Resources, 2018)

The complete mitochondrial genome of Chinese Shrew, Sorex sinalis (Soricidae) - Xuming Wang; Fengjun Li; Qi Zhang; Haijun Jiang; Shunde Chen; Shaoying Liu (Conservation Genetics Resources, 2018)

Spatial and temporal variation of the near‐surface wind environment in the dune fields of northern China - Xujia Cui; Zhibao Dong; Hu Sun; Chao Li; Fengjun Xiao; Zhengyao Liu; Shaopeng Song; Xiaolan Li; Nan Xiao; Weiqiang Xiao (International Journal of Climatology, 2018)
Research on the wind environment provides an important reference for tackling desertification and related environmental issues in desert regions. This article examines spatial and temporal variation of the near‐surface wind environment in the dune fields of northern China, using data from 40 meteorological stations inside and around the dune fields. Wind speed series were first subjected to homogenization, with monthly mean wind speed of the highly correlated neighbour stations as reference series. We found that the homogenized wind speed trends were approximately in accordance with the raw wind speed trends. The wind environment showed spatial and temporal differences, but wind speed has generally decreased both annually and seasonally since 1960, with an average trend of −0.193 m s −1 decade −1 . Mean wind speed (1960–2014) and maximum wind speed (1975–2014) decreased significantly, with distinct seasonal differences. The decreasing trend depended strongly on a decreased wind of speeds >5 m s −1 and its frequency. Overall, 48.7–80.8% of the decrease resulted from decreases in the maximum wind speed. Thus, decreases in the maximum wind speed were the dominant change in the study area. We also found that two thirds of the decrease in the drift potential primarily resulted from decreases in three prevailing wind groups (northwest, west, and south winds). This resulted from changes in the East Asian monsoon and westerly circulation. Mean air and ground surface temperatures (1960–2014) increased significantly and were significantly negatively correlated with mean wind speed, whereas sunshine duration (1960–2014) decreased significantly and was significantly positively correlated with mean wind speed. Both correlations reveal that an increasing of atmospheric dust may be responsible for the weakened wind environment. However, China's widespread sand‐control and ecological construction projects have increased ground roughness.

Location characteristics and differentiation mechanism of logistics nodes and logistics enterprises based on points of interest (POI): A case study of Beijing - Guoqi Li; Fengjun Jin; Yu Chen; Jinjuan Jiao; Sijing Liu (Journal of Geographical Sciences, 2017)

Spatial coupling analysis of regional economic development and environmental pollution in China - Li Ma; Fengjun Jin; Zhouying Song; Yi Liu (Journal of Geographical Sciences, 2013)

China’s regional transport dominance: Density, proximity, and accessibility - Fengjun Jin; Chengjin Wang; Xiuwei Li; Jiao’e Wang (Journal of Geographical Sciences, 2010)